Acute nonspecific (musculoskeletal) low back pain Guidelines of the Russian Society for the Study of Pain (RSSP) - V. A. Parfenov (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2018)
The examination of a patient with acute low back pain (LBP) includes the clarification of complaints and history data, brief physical and neurological examinations, and an assessment of danger symptoms. The diagnosis of acute nonspecific (musculoskeletal) LBP is based on the exclusion of a specific cause of pain (a potentially dangerous disease), discogenic radiculopathy, and lumbar spinal stenosis. If there is typical musculoskeletal pain and no danger symptoms, radiography, X-ray computed tomography, and magnetic resonance imaging are not recommended in the first 4 weeks of disease. Whether it is expedient to perform these techniques is considered when LBP persists over this time period. A patient with acute nonspecific (musculoskeletal) LBP should be informed about the favorable outcome of the disease and the need to maintain physical and social activities, to avoid bed rest, and, if possible, to continue professional activities. The lowest effective dose of nonsteroidal anti-inflammatory drugs for short-term duration, as well as muscle relaxants (the medium level of evidence) can be used to relieve pain. It is recommended that one should use an educational program (to prevent over-exercising and prolonged standing or sitting in static and awkward positions; to lift weights properly; etc.) to prevent recurrent LBP, as well as therapeutic exercises during a non-exacerbation period.